Antibiotic prophylaxis in preterm premature rupture of membranes at 24–31 weeks' gestation: Perinatal and 2‐year outcomes in the EPIPAGE‐2 cohort. (13th January 2022) - Lorthe, Elsa; Letouzey, Mathilde; Torchin, Héloïse; Foix L'Helias, Laurence; Gras‐Le Guen, Christèle; Benhammou, Valérie; Boileau, Pascal; Charlier, Caroline; Kayem, Gilles; ,
Abstract: Objective: To compare different antibiotic prophylaxis administered after preterm premature rupture of membranes to determine whether any were associated with differences in obstetric and/or neonatal outcomes and/or neurodevelopmental outcomes at 2 years of corrected age. Design: Prospective, nationwide, population‐based EPIPAGE‐2 cohort study of preterm infants. Setting: France, 2011. Sample: We included 492 women with a singleton pregnancy and a diagnosis of preterm premature rupture of membranes at 24–31 weeks. Exclusion criteria were contraindication to expectant management or indication for antibiotic therapy other than preterm premature rupture of membranes. Antibiotic prophylaxis was categorised as amoxicillin ( n = 345), macrolide ( n = 30), third‐generation cephalosporin ( n = 45) or any combinations covering Streptococcus agalactiae and >90% of Escherichia coli ( n = 72), initiated within 24 hours after preterm premature rupture of membranes. Methods: Population‐averaged robust Poisson models. Main Outcome Measures: Survival at discharge without severe neonatal morbidity, 2‐year neurodevelopment. Results: With amoxicillin, macrolide, third‐generation cephalosporin and combinations, 78.5%, 83.9%, 93.6% and 86.0% of neonates were discharged alive without severe morbidity. The administration of third‐generation cephalosporin or any E . coli ‐targeting combinations was associated with improved survival without severe morbidity (adjusted risk ratio 1.25 [95% confidence interval 1.08–1.45] and 1.10 [95 % confidence interval 1.01–1.20], respectively) compared with amoxicillin. We evidenced no increase in neonatal sepsis related to third‐generation cephalosporin‐resistant pathogen. Conclusion: In preterm premature rupture of membranes at 24–31 weeks, antibiotic prophylaxis based on third‐generation cephalosporin may be associated with improved survival without severe neonatal morbidity when compared with amoxicillin, with no evidence of increase in neonatal sepsis related to third‐generation cephalosporin‐resistant pathogen. Tweetable Abstract: Antibiotic prophylaxis after PPROM at 24–31 weeks: 3rd‐generation cephalosporins associated with improved neonatal outcomes. Tweetable Abstract: Antibiotic prophylaxis after PPROM at 24–31 weeks: 3rd‐generation cephalosporins associated with improved neonatal outcomes.